Survival and conjugation of Bacillus thuringiensis in a soil microcosm - Vilas-Bôas, Laurival A. [UNESP]; Vilas-Bôas, Gislayne F.L.T. [UNESP]; Saridakis, Halha O.; Lemos, Manoel Victor F. [UNESP]; Lereclus, Didier; Arantes, Olivia M.N. (Oxford University Press (OUP), 2000)
The survival and conjugation ability of sporogenic and asporogenic Bacillus thuringiensis strains were investigated in broth, in non-amended sterile clay soil monoculture and in mixed soil culture. The 75 kb pHT73 plasmid carrying an erythromycin resistance determinant and a cry1Ac gene was transferred in mating broth and soil microcosm. Survival of strains was assessed in soil monoculture and in mixed soil culture for up to 20 days. Sporogenic strains rapidly formed viable spores which were maintained until the end of the experiment. The asporogenic strains were no longer recovered after 8 days of incubation. This study shows that the environmental impact of asporogenic B. thuringiensis strains is lower than that of sporogenic B. thuringiensis strains. Thus, the use of asporogenic strains may significantly reduce any potential risk (gene transfer, soil and plant contamination) due to the dissemination of B. thuringiensis-based biopesticides in the environment. Copyright (C) 2000 Federation of European Microbiological Societies.
Keywords: Bacillus thuringiensis; Conjugation; Plasmid; Soil microcosm; Sporulation mutant; microcosm; soil microorganism; survival; bacterium conjugation; ecosystem; gene transfer; mating; mutant; nonhuman; plasmid; priority journal; soil; sporogenesis